2017
DOI: 10.1021/acsmedchemlett.6b00423
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of [1,2,3]Triazolo[4,5-d]pyrimidine Derivatives as Novel LSD1 Inhibitors

Abstract: Lysine specific demethylase 1 (LSD1) plays a pivotal role in regulating the lysine methylation. The aberrant overexpression of LSD1 has been reported to be involved in the progression of certain human malignant tumors. Abrogation of LSD1 with RNAi or small molecule inhibitors may lead to the inhibition of cancer proliferation and migration. Herein, a series of [1,2,3]triazolo[4,5-]pyrimidine derivatives were synthesized and evaluated for their LSD1 inhibitory effects. The structure-activity relationship studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…In this context, Diao and collaborators synthesized a series of diethylene glycol tethered isatin-1,2,3-triazole-coumarin derivatives (22a-l, Figure 11) [50]. Several isatin-based or 1,2,3-triazole or coumarin-based compounds (semaxanib, carboxyamidotriazole and STX64) are involved in clinical trials or have already been used the treatment of various cancers (as colon-rectal, prostatic, endometrial and breast cancer) [51,52], whereas isatin-1,2,3-triazole-coumarin derivatives showed activity against different cancer types. In addition, SAR studies demonstrated that the linker between isatin and 1,2,3-triazole influences the activity [52,53] and that hydrogen bonds are fundamental for the biological activity [54].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…In this context, Diao and collaborators synthesized a series of diethylene glycol tethered isatin-1,2,3-triazole-coumarin derivatives (22a-l, Figure 11) [50]. Several isatin-based or 1,2,3-triazole or coumarin-based compounds (semaxanib, carboxyamidotriazole and STX64) are involved in clinical trials or have already been used the treatment of various cancers (as colon-rectal, prostatic, endometrial and breast cancer) [51,52], whereas isatin-1,2,3-triazole-coumarin derivatives showed activity against different cancer types. In addition, SAR studies demonstrated that the linker between isatin and 1,2,3-triazole influences the activity [52,53] and that hydrogen bonds are fundamental for the biological activity [54].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Further mechanistic studies showed compound 7 inhibited cell migration and evasion, induced apoptosis and robustly suppressed growth of MGC-803 cells overexpressing LSD1 in vivo without significant toxicity. Following this work, our group recently performed extensive SARs studies using the scaffold hopping and bioisosteric replacement strategies, leading to the discovery of new LSD1 inhibitors 8 and 9, which reversibly inhibited LSD1 with the IC 50 values of 154 and 564 nM [57,58]. Compound 8 concentrationdependently inhibited migration of A549 and PC-9 future science group Advances toward LSD1 inhibitors for cancer therapy Review cells, but exerted different effects on the expression levels of E-cadherin and N-cadherin.…”
Section: Glu 379mentioning
confidence: 99%
“…The synthetic route of the title compounds is demonstrated in Scheme 1 . The starting chlorides 1 were prepared from 4,6-dihydroxy-2-mercaptopyrimidine within 6 steps according to the previously reported methods 14 , 15 , 16 . And the target compounds 3 – 24 were readily prepared in 70%–90% yields by reacting 1 with different amines 2 under alkaline conditions.…”
Section: Resultsmentioning
confidence: 99%